Hydrolytic Enzyme Producing Bacteria From The Gut Of Oryctes rhinoceros Larvae Inhabiting Household Waste Composer - Ana Mariatul Khiftiyah; Ni'matuzahroh; Mochammad Affandi; Salamun; Silvia Kurnia Sari; Miftahul Jannah; Nastiti Trikurniadewi; Achmad Zainal Abidin; Nurul Wahyuni; Rizki Amaliah Zain; Dela Dwi Alawiyah; Brigita Nur Diyan Agustiana (Journal of Bio-Molecule Research and Engineering, 2023)
relatively shorter adult phase than the larval stage. The larval stage of this organism lives in piles of organic matter, including in piles of household waste. The ability of larvae to utilize organic matter in their environment is inseparable from the role of potential microbes that produce enzymes associated with their gut. This study aims to isolate, screen, and identify the potential bacteria in producing hydrolytic enzymes from gut of O. rhinoceros larvae. The third instar larvae were dissected aseptically to obtain gut bacterial isolates. The isolates were tested for their ability to produce amylase, cellulose, lipase, and protease using agar plate containing specific substrates. There were eight different isolates, and three of them had the ability to produce all four enzymes. The three isolates were identified as Bacillus. These results can be used as a reference for handling household organic waste.